Reducing HIV infection in people who inject drugs is impossible without targeting recently-infected subjects. (28th November 2016) - Vasylyeva, Tetyana I.; Friedman, Samuel R.; Lourenco, Jose; Gupta, Sunetra; Hatzakis, Angelos; Pybus, Oliver G.; Katzourakis, Aris; Smyrnov, Pavlo; Karamitros, Timokratis; Paraskevis, Dimitrios; Magiorkinis, Gkikas
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Although our understanding of viral transmission among people who inject drugs (PWID) has improved, we still know little about when and how many times each injector transmits HIV throughout the duration of infection. We describe HIV dynamics in PWID to evaluate which preventive strategies can be efficient. Design: Due to the notably scarce interventions, HIV-1 spread explosively in Russia and Ukraine in 1990s. By studying this epidemic between 1995 and 2005, we characterized naturally occurring transmission dynamics of HIV among PWID. Method: We combined publicly available HIV pol and env sequences with prevalence estimates from Russia and Ukraine under an evolutionary epidemiology framework to characterize HIV transmissibility between PWID. We then constructed compartmental models to simulate HIV spread among PWID. Results: In the absence of interventions, each injector transmits on average to 10 others. Half of the transmissions take place within 1 month after primary infection, suggesting that the epidemic will expand even after blocking all the post–first month transmissions. Primary prevention can realistically target the first month of infection, and we show that it is very efficient to control the spread of HIV-1 in PWID. Treating acutely infected on top of primary prevention is notably effective. Conclusion: As a large proportion of transmissions among PWID occur within 1 month after infection, reducing and delaying transmissions through scale-up of harm reduction programmes should always form the backbone of HIV control strategies in PWID. Growing PWID populations in the developing world, where primary prevention is scarce, constitutes a public health time bomb.